The impact of “Family 500+” benefit programme on the birth rate in Poland - Ćwiąkała-Małys, Anna; Mościbrodzka, Monika (Wydawnictwo Uniwersytetu Wrocławskiego, 2024)
The aim of this work is to examine the impact of the introduced “Family 500+” benefit programme and its continuation (“Family 800+”) on the birth rate in Poland with the use of dynamic econometric modelling.
Keywords: “Family 500 ” benefit; social programme; birth rate; fertility index; demography